ANALISIS KINERJA SUPPLY CHAIN MANAGEMENT BERDASARKAN STUDI LITERATUR DENGAN PENDEKATAN SCOR - Shine Highest; Hillary Tanessa; Satrio Ariel Pratama; Nidya Banuari (MTU PRESS, 2026)
Supply chain management plays an important role in improving operational performance and company competitiveness. This study aims to analyze supply chain performance based on previous research. The method used is a literature review of several national journals discussing supply chain performance measurement using the Supply Chain Operations Reference (SCOR) approach. The results show that most companies have moderate supply chain performance, with main problems in planning, sourcing, and distribution. The SCOR model provides a structured and comprehensive overview of supply chain performance. Keywords: supply chain performance, supply chain management, SCOR